Tengrianism in the history and culture of the nomads of Central Asia - Ulanov, Mergen S. (The New Research of Tuva, 2022)
The article deals with the issue of the role of Tengrianism in the history and culture of the nomads of Central Asia. The origin of Tengrianism is usually associated with the Hunnu (Xiongnu) people who created a large nomadic realm in this region. Tengrianism gained further development already in the age of the great Turkic khaganates where the ancestors of contemporary Turkic and Mongolian peoples lived. The final formation of Tengrianism as an imperial religion is associated with the emergence of new nomadic empires. Ancient Turkic runic monuments testify to the close connection of the Tengrian cult of Heaven with authority and the state.During the formation of the Mongol Empire, the imperial cult of Heaven and the Tengrian ideology were again in demand, because they justified the legitimacy of the new government by the “will of Heaven” and united the diverse tribes and peoples of the Great Steppe with a common worldview. The cult of Heaven under Genghis Khan actually turned into an official religion which at the same time did not negate other confessions. Thereafter, Tengrianism as a politicized religious tradition gradually declined, giving way to Mahayana Buddhism, Islam, and shamanism.An important element of the Tengrian teaching was the covenant to live in agreement and harmony with the natural world and its laws. Tengrianism, being a transitional stage from early religious forms to more advanced religions, had not yet developed a full-fledged system of theology and morality. Therefore, the nomads were focused primarily on the earthly life and not on the afterlife. With the help of cultural codes, Tengrianism was developing and maintaining specific mental characteristics in the nomadic society.The author notes the connection between Tengrianism and the white shamanism of the peoples of Siberia, pointing out that white shamans and Tengri priests performed preeminently social rituals, worshipped gods of the Upper world, wore the same white clothes and rode white horses. The cult of the White Old Man — popular among the Mongolian peoples and Tuvans — is probably connected with Tengrianism.The interaction of Tengrianism with Buddhism and shamanism is considered within the framework of the doctrine of the Apollonian and Dionysian principles that was developed by Friedrich Nietzsche. In this regard, Tengrianism, as well as Buddhism, can be defined as an Apollonian type of religion, while shamanism is a religious Dionysianism.
Keywords: Tengrianism; shamanism; Buddhism; nomads; Mongolian peoples; Turkic peoples; Mongols; Apollonianism; Dionysianism